Towards Tonality: Aspects of Baroque Music Theory - Dejans, Peter; Beelaert, Sylvester; Snyers, Kathleen; Christensen, Thomas; Gouk, Penelope; Geay, Gerard; McClary, Susan; Jans, Markus; Lester, Joel; Vanscheewijck, Marc (Leuven Leuven University Press, 2007)
This is a collection of essays based on lectures presented at the International Orpheus Academy for Music & Theory on "Historical Theory, Performance, and Meaning in Baroque Music", 14-18 April, 2004.The often complex connections and intersections between, e.g., modal and tonal idioms, contrapuntal and harmonic organisation, are considered from various perspectives as to the transition (towards tonality) from the Renaissance to the Baroque era.
Preface -- Genres of Music Theory, 1650-1750 / Thomas Christensen -- Science and Music, or the Science of Music: Some Little-known Examples of "Music Theory" Between 1650 and 1750 / Penelope Gouk -- L'édition de la polyphonie française du 17e siècle / Gérard Geay -- Towards a History of Harmonic Tonality / Susan McClary -- Towards a History of the Origin and Development of the Rule of the Octave / Markus Jans -- Thoroughbass as a Path to Composition in the Early Eighteenth Century / Joel Lester -- Giovanni Paolo Colonna and Petronio Franceschini: Building Acoustics and Compositional Style in Late Seventeenth-Century Bologna -- Personalia -- Colophon
Keywords: 17th Century (1601-1700); 18th Century (1701-1800); Harmony; Tonality; Music history; Cultural history; Publishing; Polyphony; Basso continuo; Rule of the octave; Acoustics; Europe; France; Bologna (Italy)